Variability of 1000-grain weight and productivity of mutant populations of spring common WHEAT (Triticum aestivum L.) in the northern Trans-Urals - N. A. Bome; S. Salekh; L. I. Vaisfeld (Зерновое хозяйство России)
The purpose of the current study was to determine the variability of 1000-grain weight of mutant samples of the fifth (M5), sixth (M6) and seventh (M7) generations of spring common wheat (Triticum aestivum L.) in correlation with other traits in the Northern Trans-Urals. During three growing seasons (2021–2023), 29 mutant samples of the fifth (M5), sixth (M6), and seventh (M7) generations were tested in field trials. Mutations were induced using the chemical mutagen phosphemid after treating seeds of the varieties ‘Scant 3’ (Russia), ‘Cara’ (Mexico), and the hybrid F4 (‘Cara’ x ‘Scant 3’). There have been established significant differences in 1000-grain weight and grain productivity among mutants that exceeded the original forms. High indicators of the trait ‘1000-grain weight’ were found in promising mutants compared to zoned (control, standard) varieties (‘Tyumenskaya 25’, ‘Tyumen- skaya 29’, ‘Novosibirskaya 31’). There has been identified a reliable (p < 0.05) positive correlation between 1000-grain weight and productivity (r = 0.680–0.760), grain weight per ear (r = 0.691–0.703), plant height (r = 0.478–0.586), width (r = 0.370–0.371) and area (r = 0.391) of a flag leaf, number of plants (r = 0.342) and productive shoots (r = 0.336) per 1 m2, and a negative correlation with length of ears (r = -0.493) and number of grains per ear (r = -0.387). The study results of variability and correlation between traits has shown that the trait ‘1000-grain weight’ can be used as a parameter for selecting valuable genotypes. The mutants with the best grain size and productivity, with good indices protein and hardiness represent a genetic resource for spring common wheat breeding programs in certain agroecological conditions.